Técnica FAST (Focused Assessment with Sonography for Trauma) e VetBLUE (Veterinary Bedside Lung Ultrasound Exam) na prática veterinária de pequenos animais: Revisão de Literatura - Marim, Isabelle Almeida [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
A técnica FAST Focused Assessment with Sonography in Trauma) e a técnica Vet BLUE(Veterinary Bedside Lung Ultrasound Exam) são exames ultrassonográficos de técnicas relativamente simples que buscam avaliar a presença de líquido livre em abdome, tórax e pericárdio, assim como a presença de edema, pneumotórax e consolidações em pulmão. São técnicas amplamente utilizadas na rotina médica de emergência e cuidados intensivos por ser rápida, não invasiva e pouco custosa. Os exames fornecem informações essenciais para a conduta médica imediata, reduzem a necessidade de manipulação do animal e possuem sensibilidade e especificidade satisfatória quando comparadas com outros exames de imagem. São técnicas que podem ser utilizadas em conjunto e cresceram muito na medicina veterinária de emergência nas últimas décadas.

The FAST (Focused Assessment with Sonography in Trauma) technique and the Vet BLUE (Veterinary Bedside Lung Ultrasound Exam) technique are relatively simple ultrasound exams aimed at evaluating the presence of free fluid in the abdomen, thorax, and pericardium, as well as detecting pulmonary edema, pneumothorax, and lung consolidations. These techniques are widely used in emergency and intensive care medical routines due to being fast, non-invasive, and low-cost. The exams provide essential information for immediate medical decision-making, reduce the need for handling the animal, and have satisfactory sensitivity and specificity when compared to other imaging modalities. These techniques can be used together and have seen significant growth in veterinary emergency medicine over the past decades.
FAST (Focused Assessment with Sonography for Trauma) and VetBLUE (Veterinary Bedside Lung Ultrasound Exam) technique in small animal veterinary practice: Literature Review
Keywords: FAST; VetBLUE; Ultrassonografia; Emergências; Intensivismo